The Relationship of Cyberbullying and Self-Harm Behavior Among Adolescents - Jannah, Safira Salsabilul; Septianawati, Paramita; Immanuel, Glorio; Mustikawati, Irma Finurina (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2024)
Cyberbullying phenomenon among adolescents have been one of the significant outcome of 21st-century technological advancements. The widespread use of social media in cyberspace has made it easier for perpetrators to engage in various forms of digital harassment, which can lead individuals to conduct self-harm. Therefore, the researcher observes the potential of cyberbullying has a significant impact on self-harm. Thus, it is necessary to conduct research linking the two. This study employs an analytical observational research type with a cross-sectional approach. The population for this research consists of adolescents at SMPN 1 Purwokerto, with sampling conducted using a non-probability sampling method, specifically consecutive sampling. The results indicate that the highest role of respondents in cyberbullying is as victims (56%). The frequency distribution data shows that the highest intensity of involvement in cyberbullying falls into the mild category, with 111 respondents (74%). The number of self-harm doers is 100 respondents (66%). The study provides evidence of a positive correlation between cyberbullying incidents and self-harm behavior among adolescents.